Decadal variability in growth of the Caribbean spiny lobster Panulirus argus (Decapoda: Paniluridae) in Cuban waters - de León, María Estela (2005)
Annual von Bertalanffy growth parameters of the Caribbean spiny lobster (Panulirus argus) in Cuban waters were estimated from a long term study (40 years) by length-based methods ELEFAN and the new version of SLCA. Data of around 800 000 lobsters (with carapace length ranging 14 to 199mm) were randomly sampled in artificial shelters (a non selective fishing gear very common in the lobster fishery), through the field monitory program established for this species since 1963 in 14 localities of southwestern Cuban shelf. The software ELEFAN showed problems to converge in an optimal combination of the instantaneous growth coefficient (K) and the asymptotic length (L∞) of the von Bertalanffy equation, whereas the new SLCA software produced value estimates of K between 0.20 and 0.27 year-1 and values of L∞ between 177 and 190 mm carapace length, all within the range reported in the literature. The standardized anomalies of both parameters showed the presence of cycles along the analyzed time series. Decadal variability in growth parameters was revealed through the spectral analysis indicating cycles of 16 and 20 years for K and of 16 years for L∞. The incidence of some factors such as biomass and temperature that modulate growth in this crustacean was explored, using a nonlinear multiple regression model. These combined factors explained 33% and 69% of the variability of K and L∞ respectively. The growth coefficient appeared to be maximum with annual mean sea surface temperature of 28.1º C and the largest L∞ is reached at a annual men biomass level of 23 000 t. These results should be the basis to understand the Cuban lobster population dynamics.